Resisting and conforming to the ‘lesbian look’: The importance of appearance norms for lesbian and bisexual women - Huxley, Caroline; Clarke, Victoria; Halliwell, Emma (Journal of Community & Applied Social Psychology, 2014)
Appearance is one way in which lesbian and bisexual identities and affiliation to lesbian, gay, bisexual (LGB) subculture can be demonstrated. ‘Butch’ and ‘androgynous’ styles have been used by lesbian women to communicate a non-heterosexual identity. However, some LGB appearance researchers have argued that there has been a mainstreaming and diversification of lesbian style in the last couple of decades, which has resulted in less distinction between lesbian and straight looks. This research draws on the Social Identity approach to explore contemporary style in lesbian and bisexual communities. Fifteen lesbian and bisexual women took part in semi-structured interviews which were analysed using thematic analysis. Although some participants reported a diversification of lesbian style, most used the term ‘butch’ to describe lesbian style, and a ‘boyish’ look was viewed as the most common contemporary lesbian style. By contrast, most participants could not identify distinct bisexual appearance norms. The data provide evidence of conflicting desires (and expectations) to visibly project social identity by conforming to specific lesbian styles, and to be an authentic, unique individual by resisting these subcultural styles
Keywords: 2000 à aujourd'hui; 2010-2019; discipline; europe; identités LGBTQIA2+; psychologie; périodes historiques; ressource en ligne; royaume-uni; régions géographiques; sciences humaines